A Study on the Beneficiation of Very Fine Particle Rutile Ore Using Flotation - Bilgin, Oyku; Ehsani, Ilhan (Mdpi, 2025)
This study investigates the beneficiation of finely grinded rutile ore utilizing a combination of flocculation and flotation methods. Rutile, a Ti-bearing mineral with industrial significance, is often associated with heavy minerals found in coastal and metamorphic environments. A rutile ore sample from Az & imath;tepe (Ala & scedil;ehir, T & uuml;rkiye) was reduced to -63 mu m and enriched under varying pH conditions (2.5-12) using different reagent combinations and was used for our investigation of both flocculation and flotation processes using reagents such as Aero801(SIPX), Aero825, tannic acid (TA), and pomace oil. The best results were achieved at pH: 8 using Aero801(SIPX) and pomace oil during flocculation, and Aero801(SIPX), Aero825, and Aerofroth88 during flotation, yielding a concentrate with an 8.99% TiO2 grade and an 89.5% recovery rate. Meanwhile, a 7.00% TiO2 grade concentrate was obtained with a recovery rate of 71.92% at neutral pH. This study found that pH and reagent selection had an important effect on TiO2 enrichment efficiency in fine size, low-grade rutile ores. Future research is recommended to investigate selective depressants and multi-stage cleaning to improve separation.
Keywords: rutile; titanium; beneficiation; flotation